CPW-Fed Dual Band Flexible Antenna for Energy IoT Applications at 380/940 MHz - Soyeong Lee; Sangjoon do; Hoosung Lee; Daeyeong Yoon; Yong Bae Park (IEEE Access)
In this paper, we present the design and fabrication of a dual-band flexible antenna for energy Internet of Things (IoT) applications operating at 380 MHz and 940 MHz. The antenna features a coplanar waveguide (CPW) feed structure and a T-shaped monopole design on a polyimide substrate, with tapered stepped ground plane and square ring-shaped parasitic elements to minimize performance degradation due to bending. The antenna size is $210× 236× 0.2$ mm3, achieving bandwidths of 25.2% ( $344\sim 440$ MHz) and 15.2% ( $863\sim 1006$ MHz) when flat, with peak gains of 2.52 dBi and 4.90 dBi, respectively. We evaluate the antenna’s performance under various bending conditions using cylindrical styrofoam structures with radii of 25, 35, 45 cm, and the bandwidth degradation is within 4%. To verify the realistic applicability in energy IoT applications, we perform performance analysis considering a transmission tower environment with a cylindrical metal structure having a diameter of 60 cm, ensuring that performance degradation is minimized at a distance of at least 5 cm from the metal structure. Link margin calculations for Korea Electric Power Corporation (KEPCO)’s IoT specifications demonstrate values of 34.08 dB at 380 MHz and 31.94 dB at 940 MHz, confirming the antenna’s suitability for KEPCO’s energy IoT applications. These results indicate that the proposed antenna meets the requirements for efficient operation in KEPCO’s IoT infrastructure.